Enhancing gene transfer to renal tubules and podocytes by context-dependent selection of AAV capsids - Taisuke Furusho; Ranjan Das; Hideyuki Hakui; Anusha Sairavi; Kei Adachi; Mia S. Galbraith-Liss; Pratheppa Rajagopal; Masahiro Horikawa; Shuhua Luo; Lena Li; Kentaro Yamada; Nicole Andeen; et al. (Nature Communications)
Abstract AAV vectors show promise for gene therapy; however, kidney gene transfer remains challenging. Here we conduct a barcode-seq-based comparison of 47 AAV capsids administered through different routes in mice, followed by individual validation. We find that local delivery of AAV-KP1, but not AAV9, via the renal vein or pelvis effectively transduces proximal tubules with minimal off-target liver transduction, while systemic AAV9, but not AAV-KP1, enhances proximal tubule and podocyte transduction in chronic kidney disease. We demonstrate that these contrasting observations are partly due to differences in their pharmacokinetics. Importantly, we show that renal pelvis injection overcomes pre-existing immunity, leading to robust and exclusive proximal tubule transduction, in non-human primates (NHPs). In addition, we highlight drastic differences in renal transduction profiles between mice and NHPs. Thus, this study provides mechanistic insights and underscores importance of context-dependent selection of AAV capsids to overcome challenges in gene delivery to the kidney.